2011
DOI: 10.1108/09526861111139205
|View full text |Cite
|
Sign up to set email alerts
|

The effect of changes in servicescape and service quality perceptions in a maternity unit

Abstract: There is agreement that the servicescape affects perceptions of service quality and this study bears out this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…This was uninspiring, sparse, and uncomfortable, and a new environment featuring plants, floor lamps, and comfortable sofas, where people could feel more at ease, was created. With cases such as these, it is difficult not to concur with Holder and Berndt ( ), who suggest that there is now increasing evidence available to indicate that the nature of the servicescape can influence favorably the emotions and physical health of patients.…”
Section: Service Design and Delivery: Unravelling The Health Servicesmentioning
confidence: 92%
See 1 more Smart Citation
“…This was uninspiring, sparse, and uncomfortable, and a new environment featuring plants, floor lamps, and comfortable sofas, where people could feel more at ease, was created. With cases such as these, it is difficult not to concur with Holder and Berndt ( ), who suggest that there is now increasing evidence available to indicate that the nature of the servicescape can influence favorably the emotions and physical health of patients.…”
Section: Service Design and Delivery: Unravelling The Health Servicesmentioning
confidence: 92%
“…Research has demonstrated that the nature of the service-setting patients' experience is one of the most significant determinants of perceived quality, which can lead to both competitive advantage for the provider (Taylor, 1994) and the longterm loyalty of the consumer (Otani, Waterman, Faulkner, Boslaugh, & Dunagan, 2010). This service environment, made up of the tangibles of buildings, furnishings, layouts, and various signs and the intangibles of temperature, color, scent, and music, has been found to impact directly on the perceptions of health-service quality, from the perspectives of physicians, patients, and health-care decision makers (Department of Health, 2005;Holder & Berndt, 2011;Jun, Peterson, & Zsidism, 1998). If we add to this the actions of clinicians and their interactions with users (Fottler, Ford, Roberts, Ford, & Spears, 2000), then there is an entire service setting that represents what the consumer is seeking, and in many cases paying for, from the total health-care experience.…”
Section: Service Design and Delivery: Unravelling The Health Servicmentioning
confidence: 99%
“…SERVPERF, an alternative methodology to SERVQUAL, appears to have a good fit and more construct-valid explication of service quality [42], [45]. SERVPERF is also actively employed in the context of healthcare services [45]- [47].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patient experience deals with all aspects of the perceptions of patients and their families and ranging from safety, quality of food, friendliness of staff; quality of food to physical surroundings. Perceptions of the physical surroundings are important due to the effect the physical evidence has on patient and on their perceptions of service quality (Harris & Ezeh, 2008;Holder & Berndt, 2011).…”
Section: Racial and Ethnic Disparities In Health Carementioning
confidence: 99%
“…Or as non-living features that comprise the service environment (Zeithaml, Bitner & Gremler, 2006;Hofmann, Bateson, Wood & Kenyon, 2009;Countryman & Yang, 2006;Lovelock & Wright, 2002;Holder & Berndt, 2011). It is thus clear that the services that are rendered within the tangible construct (physical environment) may have a significant influence on the satisfaction levels experienced by patients in a public healthcare setting.…”
Section: The Tangible Environment Of Health Carementioning
confidence: 99%